2022
DOI: 10.1038/s41416-022-02053-5
|View full text |Cite
|
Sign up to set email alerts
|

UK Biobank: a globally important resource for cancer research

Abstract: UK Biobank is a large-scale prospective study with deep phenotyping and genomic data. Its open-access policy allows researchers worldwide, from academia or industry, to perform health research in the public interest. Between 2006 and 2010, the study recruited 502,000 adults aged 40–69 years from the general population of the United Kingdom. At enrolment, participants provided information on a wide range of factors, physical measurements were taken, and biological samples (blood, urine and saliva) were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 78 publications
0
32
0
Order By: Relevance
“…It has been shown that the UKB is a valuable resource for evaluating the utility of PRS, as it provides both phenotypic and genotypic data (28). While the majority of UKB participants have EUR ancestry, the dataset involves more than 20,000 participants of self-reported non-EUR.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the UKB is a valuable resource for evaluating the utility of PRS, as it provides both phenotypic and genotypic data (28). While the majority of UKB participants have EUR ancestry, the dataset involves more than 20,000 participants of self-reported non-EUR.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of information on cancer treatment is a significant limitation of this study, especially given the potential effect of chemotherapy and hormone therapy on brain structures 13,14,49 . While UK Biobank is linked to the UK national cancer registries, which are regarded as the gold standard for identifying cancer outcomes in the United Kingdom, the completeness of data might experience a time lag due to the complicated curation process from multiple sources 50 . UK Biobank has future plans to expand its linkage, aiming to incorporate information on cancer treatment, which can serve as a step toward addressing our current limitation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the UK Biobank, with information on 500,000 individuals, includes more than 52,000 incident cancer cases in the cohort. [45][46][47] In the United States, analysis of data representing 203,813 participants enrolled in the All of Us research program for whom EHR data were available identified 23,520 cancer cases. 48,49 These programs combine all the needed elements for discovery; however, they are typically composed of mostly healthy volunteers and it is unclear, despite the relatively large cohort size, if the number of individuals comprising ancestral subgroups with a relevant disease and drug exposure would be sufficient to identify novel PGx associations.…”
Section: And References Therein)mentioning
confidence: 99%